Fagopyrum caudatum var. grandiflorum, a new variety from China - Li, Wei; Zhang, Kaixuan; Tang, Yu; Ding, Mengqi; Wen, Wen; Li, Bo; Zhou, Meiliang (Phytotaxa, 2023)
A new variety of Fagopyrum caudatum—Fagopyrum caudatum var. grandiflorum—is described and illustrated from Longnan City, Gansu Province, China. The new variety could be easily distinguished from F. caudatum var. caudatum mainly by its larger flower size (5.3–5.6 mm vs. 3.2–3.5 mm). The detailed description and photographs of the new variety were provided.